Microsoft Office 365 all-in-one - McFedries, Paul (John Wiley & Sons, Inc., 2025)
Provides detailed coverage of each Office 365 module and offers advice on optimizing the applications, including Word, Excel, PowerPoint, Outlook, Publisher, and Access.
"8 books in one!"--Cover. - Includes index. - Print version record
Keywords: Microsoft Office; Business -- Computer programs; Integrated software; Logiciels intégrés